The Involvement of Mary Magdalene in the Sacrificial Death of Jesus on The Cross: Lessons for the Nigerian Christian Women - Jibromah Oghenekevwe K.; Sangotunde Sunday O (European Scientific Journal, ESJ, 2018)
One major concept that runs through all religious institutions and communities is the practice of ‘sacrifice’. This idea also runs through both the Old and the New Testaments. The world in which the Bible authors inhabited was filled with physical equipments and sacred spaces of sacrifices, from massive temple to rustic country shrines, to tiny household altars. It was made up of interwoven relationships that were reinforced by sacrificial practices. Throughout the book of Leviticus, the idea of appeasement of Yahweh through series of sacrificial acts perfused the entire pages of the book. The death of Jesus Christ on the cross as the final sacrificial rite is the foundation of the Christian faith. Women are generally not considered as occupying important position in the Jewish religious culture and this idea is almost transmitted into the religious arrangement of many denominations today due to some complexities engendered by Paul’s teachings in some of his epistles. Women had played major role on Christ sacrificial death on the cross, although little has been mentioned about them. Hence, the study investigates women’s involvement during Christ crucifixion on the cross focusing basically on Mary Magdalene. The paper adopts textural analysis of the related verses. It also makes use of exegetical method as an approach to unveil the textual relevance of the selected texts to the subject matter. It reveals the positive role played by this woman during the sacrificial death of Christ on the cross in the interface of the expected roles of Nigerian Christian women in the ecclesiastical community. The paper concludes that women played significant role during Jesus’ sacrificial death which is worthy of emulation by women participating in Christian ministries in Nigeria.